THEMARKING-OUT OF EDUCATIONALIDEAS - Survutaitė, Dalia (Acta Paedagogica Vilnensia, 2013)
With the development of societies in the ever-changing material conditions of existence, education is becoming increasingly complex. Based upon the history of pedagogy, we analyze and assess pedagogical phenomena and processes along their horizontal shift (from the emergence of humankind up to the current day), analyzing in detail pedagogical ideas, principles, and laws along the vertical shift (educational concepts, contents, planning, organization, evaluation). With the rapid expansion of school networks and the steadily increasing duration of compulsory schooling, a multitude of diverse pedagogical ideas came into being in Europe and the USA as early as late in the 19th c. Proponents of certain ideas supported each other creating a theory, i.e. a corresponding body of statements, concerning education. A serious discussion and assessment of educational theories and pedagogical experience (conceptions) took place already in the 20th c. Model (paradigm) forms were worked out for the solution of urgent repeated problems. Interest in the newly-arising philosophical conceptions accounted for the emergence of different movements in the area of pedagogy and school practice in the 20th c. Several tendencies can be distinguished in the development of the Lithuanian pedagogical thought. Educologists tried to describe a number of educational ideas by introducing different descriptions. Efforts were made to sort out and assess the educational ideas. Some authors tried to evaluate the educational ideas against the firmly consolidated philosophical conceptions. For the purpose of building a system, definite trend or direction parameters were introduced (Esmaitis, Bukauskienė, Valatkienė, Bitinas). Guided by dualism, some educologists created bi-polar classifications of the representation of educational ideas, such as east–west (Šalkauskis), or idealistic–realistic (Liaugminas), or reproductive–interpretative (Šalkauskis), or classic–unrestricted education (Bitinas), or classic–modern (Ušeckienė), or informational–creative (Lukšienė), or classic–humanistic (Bruzgelevičienė) ones. Among international research communities, a tendency towards the convergence of educational ideas has existed for several decades. A systematised holistic approach to the representation and change of diverse educational ideas and their interrelation is emerging (Vaitkevičius, Burrel, Morgan, Paulston). In this way the authors seek to offer practitioners a wide spectre of educational success stories, giving them a chance to construct individual success. Currently, eclectic adaptations of educational ideas in heterogeneous educational conditions are taking place. This fact contributes to the emergence of new conceptions out of the existing theories and contemporary paradigmatic dimensions. Thus, the quality of education demands not only the identification of educational ideas, but also the discovery of their meaning.